Citizen Centric Service at Sukabumi City Investment Office and One Stop Integrated Services - Ghefira Rachima M. Noor; Dian Purwanti; M. Rijal Amirulloh (Publik : (Jurnal Ilmu Administrasi), 2026)
This study aims to measure the level of optimization of the implementation of Citizen-Centric Services in Public Service Malls managed by the Sukabumi City Investment and One-Stop Integrated Services Office based on the perception of the public as service users. The research uses a quantitative descriptive method. Data was collected through the distribution of questionnaires to 100 respondents using incidental sampling techniques. The research instrument was compiled based on the dimensions of Carlson and Schwarz's service quality. Data analysis was carried out using a one-sample t-test with the help of the SPSS application. The results of the study show that the implementation of Citizen-Centric Services in the Sukabumi City Public Service Mall is in the optimal category. This is shown by an average value of 102.46 with a significance value of 0.001 < 0.05. The dimensions of convenience, justice, and security received the highest assessment from the community because services were considered more accessible, transparent, and non-discriminatory. However, the reliability dimension still needs to be improved, especially related to the timeliness of services and public understanding of digital services. This study concludes that the implementation of Citizen-Centric Services has contributed positively to improving the quality of public services in the Sukabumi City Public Service Mall. The findings are expected to be evaluated to improve the quality of community-oriented public services and as a reference for further studies related to the implementation of citizen-centered public services.